THE VALIDITY OF TRANSACTIONS ON THE ACTION MOBILE APPLICATION OF BANK ACEH SYARIAH, INDONESIA - Natasya, Ayla; Reza Yamani, Sayed Mohammad (JURISTA: Jurnal Hukum dan Keadilan, 2023)
Bank Aceh Syariah Banda Aceh is one of the Islamic banking institutions that has Action Mobile or mobile banking application. The application is a form of Bank Aceh Syariah service to facilitate customers in making transactions anywhere and anytime. As we see in the Action Mobile application of Bank Aceh Syariah, this study aims to determine the level of validity of transactions and customer satisfaction with the Action Mobile application at Bank Aceh Syariah Banda Aceh. The method used in this research is qualitative, for data collection by filling out distributing questionnaires with 70 respondents. From the results of this study concluded that with the Action Mobile application, it offers convenience in conducting banking transactions. The advantage of providing Action Mobile services for banks is saving the cost of printing forms that must be filled out by customers for transactions, brochures, catalogues, and replacing them with electronic data. For customers who use Action Mobile, they will get customer information in conducting banking transactions.